Perceptions of risk factors for road traffic accidents - Smith, Andrew; Smith, Hugo (Advances in Social Sciences Research Journal, 2017)
Research has identified a number of risk factors for road traffic accidents. Some of these require education of drivers and a first step in this process is to assess perceptions of these risk factors to determine the current level of awareness. An online survey examined risk perception with the focus being on driver behavior, risk taking and fatigue. The results showed that drivers’ perceptions of the risk from being fatigued was lower than the perceived risk from the other factors.